The Impact of Personal Selling by Perisai Agents on Contribution Payment Behavior of Informal Workers: The Mediating Roles of Product Knowledge, Perceived Risk, and Trust - Abdul Shoheh; Sumarwan, Ujang; Simanjutak, Megawati (Pelopor Publikasi Akademika, 2026)
Extending social security coverage to informal workers remains a significant challenge. This study examines the impact of personal selling by social security agents (Agen Perisai) on the contribution payment behavior of informal workers in Indonesia. It further investigates the mediating roles of perceived risk, product knowledge, and trust within the Stimulus–Organism–Response (S-O-R) framework. A quantitative explanatory design was employed. Data were collected from 150 informal workers registered at the BPJS Ketenagakerjaan Ceger Branch in Jakarta. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that personal selling significantly enhances perceived risk, product knowledge, and trust. However, it does not directly influence contribution payment behavior. Product knowledge fully mediates this relationship, while perceived risk and trust do not exhibit significant mediating effects. Social security agencies should shift their communication strategies from participant acquisition toward strengthening product literacy. Agents should emphasize clear and practical explanations of benefits to improve sustained compliance. This study extends the S-O-R framework in the context of public social insurance by demonstrating that cognitive factors, particularly product knowledge, play a more decisive role than affective factors in driving financial compliance among low-income informal workers.